Changes in high-density lipoprotein-carried miRNA contribution to the plasmatic pool after consumption of dietary trans fat in healthy men. (May 2017) - Desgagné, Véronique; Guérin, Renée; Guay, Simon-Pierre; Corbin, François; Couture, Patrick; Lamarche, Benoit; Bouchard, Luigi
Aim: High-density lipoproteins (HDLs) are associated to cardioprotection and transport functional miRNAs in circulation. The aim of this study is to assess whether consumption of trans fatty acids (TFAs) modifies the HDL-carried miRNA concentration and their contribution to the plasmatic pool.Methods: In a double-blind, randomized crossover controlled study, nine healthy men were fed each of three isoenergetic 4-week diets: first, rich in industrial TFAs; second, rich in TFAs from ruminants; third, low in TFAs. miRNAs were extracted from plasma and purified HDLs, and quantified by the real-time quantitative PCR (n = 87).Results: Seven HDL-carried miRNAs contributed to more than 15% of the plasmatic pool. Although no significant difference in HDL-carried miRNA concentration among diets was observed after adjustment for multiple testing, changes in the contribution to the plasmatic pool between diets were observed for miR-124-3p, miR-375, miR-150-5p and miR-31-5p (p FDR < 0.05). These miRNAs were enriched in lipid metabolism pathways.Conclusion: These microtranscriptomic variants might reflect physiological changes in HDL functions in response to diet.